A plasma membrane‐tethered transcription factor, NAC062/ANAC062/NTL6, mediates the unfolded protein response in Arabidopsis. (30th July 2014) - Yang, Zheng‐Ting; Lu, Sun‐Jie; Wang, Mei‐Jing; Bi, Dong‐Ling; Sun, Ling; Zhou, Shun‐Fan; Song, Ze‐Ting; Liu, Jian‐Xiang
Summary The accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER) triggers a well conserved pathway called the unfolded protein response (UPR) in eukaryotic cells to mitigate ER stress. Two signaling pathways, S2P‐bZIP28 and IRE1‐bZIP60, play important roles in transmitting ER stress signals from the ER to the nucleus in Arabidopsis (Arabidopsis thaliana). It is not known whether other components in the secretory pathway also contribute to the alleviation of ER stress. Here we report the identification of a plasma membrane‐associated transcription factor, NAC062 (also known as ANAC062/NTL6), as another important UPR mediator in Arabidopsis plants. NAC062 relocates from the plasma membrane to the nucleus and regulates the expression of ER stress responsive genes in Arabidopsis. Knock‐down of NAC062 in the wild‐type background confers ER stress sensitivity, while inducible expression of a nucleus‐localized form of NAC062, NAC062D, in the bZIP28 and bZIP60 double mutant (zip28zip60) background increases ER stress tolerance. Knock‐down of NAC062 impairs ER‐stress‐induced expression of UPR downstream genes while over‐expression of NAC062D‐MYC induces the expression of UPR downstream genes under normal growth condition. CHIP‐qPCR reveals that NAC062D‐MYC is enriched at the promoter regions of several UPR downstream genes such as BiP2. Furthermore, NAC062 itself is also up‐regulated by ER stress, which is dependent on bZIP60 but not on bZIP28. Thus, our results have uncovered an alternative UPR pathway in plants in which the membrane‐associated transcription factor NAC062 relays ER stress signaling from the plasma membrane to the nucleus and plays important roles in regulating UPR downstream gene expression.